From frequency of use to social integration: The mediation of routinization and infusion in Tuenti community - José L. Roldán; Manuel Jesús Sánchez-Franco; Juan C. Real (European Research on Management and Business Economics (ERMBE), 2017)
This study examines post-adoption behaviors (i.e., frequency of use, routinization and infusion) and their effects on the sense of community in the domain of social network sites. In particular, this contribution formulates mediation hypotheses, which posit how frequency of use affects social integration via routinization and infusion. The data was collected from 278 users of Tuenti, a highly-popular social network site among the Spanish college student population during the period 2006–2012. Results from partial least squares structural equation modeling (PLS-SEM) show these sophisticated types of usage are interrelated in such a way that routinization and infusion (a) fully mediate the effect of frequency of use on social integration; and (b) exert significant influences on social integration, as an active sense of belongingness to a social network site. In order to attain social integration, it is therefore essential for managers to devise strategies to foster advanced post-adoption behaviors.
Keywords: D8; M15; M21; O33; 650; Frequency of use; Routinization; Infusion; Social integration; Social network sites; Partial least squares